Virulence of Agrobacteriumtumefaciens requires lipid homeostasis mediated by the lysyl‐phosphatidylglycerol hydrolase AcvB. Issue 1 (14th November 2018) - Groenewold, Maike K.; Hebecker, Stefanie; Fritz, Christiane; Czolkoss, Simon; Wiesselmann, Milan; Heinz, Dirk W.; Jahn, Dieter; Narberhaus, Franz; Aktas, Meriyem; Moser, Jürgen
Summary: Agrobacterium tumefaciens transfers oncogenic T‐DNA via the type IV secretion system (T4SS) into plants causing tumor formation. The acvB gene encodes a virulence factor of unknown function required for plant transformation. Here we specify AcvB as a periplasmic lysyl‐phosphatidylglycerol (L‐PG) hydrolase, which modulates L‐PG homeostasis. Through functional characterization of recombinant AcvB variants, we showed that the C‐terminal domain of AcvB (residues 232–456) is sufficient for full enzymatic activity and defined key residues for catalysis. Absence of the hydrolase resulted in ~10‐fold increase in L‐PG in Agrobacterium membranes and abolished T‐DNA transfer and tumor formation. Overproduction of the L‐PG synthase gene ( lpiA ) in wild‐type A . tumefaciens resulted in a similar increase in the L‐PG content (~7‐fold) and a virulence defect even in the presence of intact AcvB. These results suggest that elevated L‐PG amounts (either by overproduction of the synthase or absence of the hydrolase) are responsible for the virulence phenotype. Gradually increasing the L‐PG content by complementation with different acvB variants revealed that cellular L‐PG levels above 3% of total phospholipids interfere with T‐DNA transfer. Cumulatively, this study identified AcvB as a novel virulence factor required for membrane lipid homeostasis and T‐DNA transfer. Abstract : In this study, we show that the virulence factor AcvB is a lysyl‐phosphatidylglycerol (L‐PG) hydrolase that controls proper L‐PG levels in A . tumefaciens membranes. Loss of AcvB results in increased L‐PG accumulation, which is accompanied with loss of virulence due to abolished T‐DNA transfer into plant cells.